Marine microbial bioremediation - Dave, Bharti P. 1956-; Dudhagara, Dushyant R. 1987-; Vala, Anjana K. 1973- (CRC Press, an imprint of the Taylor & Francis Group, LLC, 2022)
"Due to increased industrialization and urbanization, the marine ecosystem is getting contaminated and it has become imperative to save this ecosystem that is the largest. The book focuses on marine microbial remediation aspects. Major marine pollutants their effect on marine ecosystems, and their removal by ecofriendly, sustainable approach bioremediation have been included. Marine biota due to their unique traits are promising candidates for bioremediation processes. Mechanistic aspects of microbial bioremediation in marine environment have also been discussed"--Provided by publisher.